Soft Wireless Passive Chipless Sensors for Biological Applications: A Review - Mingguang Zhang; Mengyun Li; Wei Xu; Fan Zhang; Daojin Yao; Xiaoming Wang; Wentao Dong (Biosensors)
Soft wireless passive sensors have been applied in biological, engineering, and other fields due to their advantages in powerless supply and remote data transmission. External information is obtained by soft wireless passive sensors via the external coils based on electromagnetic induction. The purpose of this review paper is to outline the biological applications of soft wireless passive chipless sensors and provide a classification of wireless passive sensors and an overall explanation of the main work. Three kinds of soft wireless sensors, soft wireless passive LC-resonant sensors, soft wireless radio frequency (RF) sensors, and soft wireless surface acoustic wave (SAW) sensors, are introduced with their working principles, equitant circuits, and biological applications. Soft wireless passive sensors with integrated LC-resonant units are applied to physical quantity measurements for denoting the mapping relationship between the frequency resonance and the monitored object. Utilizing the electromagnetic field principle, RF sensors enable wireless measurements and data exchange of physical parameters. SAW sensors with piezoelectric substrates are applied to physical parameter monitoring using guided waves in monitoring objects. Soft wireless passive sensors aim to monitor biological health without an external power supply or wired data communication, which would bring increased convenience to the lives of the people who use them.